2013
DOI: 10.2134/agronj2012.0377
|View full text |Cite
|
Sign up to set email alerts
|

Water and Radiation Use Efficiencies in Sorghum

Abstract: Increasing water and radiation use efficiencies (WUE and RUE, respectively) are critical to enhance crop production. Exploring genetic variability in WUE and RUE is necessary to improve these traits. The objectives of this research were to evaluate eight sorghum [Sorghum bicolor (L.) Moench] genotypes for biomass production, WUE, and RUE and to test whether the differences in WUE among sorghum genotypes were associated with increased biomass production or decreased water use under field conditions. The WUE was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
7
37
1
Order By: Relevance
“…WUE, EY, and EWR were higher for both species in 2015, likely due to greater SWtot, GDD, and precipitation in 2015, relative to 2014. Interannual variability in WUE was explained by different biomass accumulation between growing seasons, rather than changes in total ET, which is consistent with findings in the literature (Steduto et al, 1997;Narayanan et al, 2013;Hao et al, 2014;Dietzel et al, 2015). While both species had similar total ET, the pattern of ET accumulation within the season (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…WUE, EY, and EWR were higher for both species in 2015, likely due to greater SWtot, GDD, and precipitation in 2015, relative to 2014. Interannual variability in WUE was explained by different biomass accumulation between growing seasons, rather than changes in total ET, which is consistent with findings in the literature (Steduto et al, 1997;Narayanan et al, 2013;Hao et al, 2014;Dietzel et al, 2015). While both species had similar total ET, the pattern of ET accumulation within the season (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Other investigations have found that the WUE of irrigated sweet sorghum was greater than other C4 crops at the canopy scale, but similar to other C4 crops at the leaf scale; however, the comparisons were made using previously reported WUE values for C4 crops, rather than measurements provided in a side-by-side field comparison (Steduto et al, 1997). Research has shown that WUE can vary significantly with climate conditions, complicating comparisons made across different years and climates (Narayanan et al 2013;Bernacchi & VanLoocke, 2015).…”
Section: 2c) Maize Cumulative Et Was Eclipsed By Biomass Sorghum Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation farming improved soil moisture, yield and water use efficiency of crops such as Winter wheat, (He et al, 2011;Hou et al, 2012). Narayanan et al (2013) evaluated eight Sorghum genotypes for biomass production, water productivity (WP) and RUE and concluded that WP was more strongly correlated to biomass production than to crop water use and that WP can be improved without compromising biomass production. RUE of grass was found to respond rapidly to soil moisture content and strong dependence of RUE on soil SWS and air temperature has also been reported (Potters et al, 1999;Tserenpure et al, 2012;).…”
Section: Soil Water Storage Conservation Practicementioning
confidence: 99%
“…The fIPAR of the measured data (Fi) was determined by using Eqn. 1: The λ of the crop for each treatment was determined by using Equation 2 with intercept set at zero because PARabove is equal to the PARbelow when LAI = 0 and the slope of each graph was taken as the seasonal λ (Narayanan et al, 2013;Robertson et al, 2001;Farahani, 2009):…”
Section: Lai and Fiparmentioning
confidence: 99%